Directions of Research on Behaviours and Purchasing Decisions of Contemporary Consumers From In Light of Available Research Results - Anita PROSZOWSKA (Communications of International Proceedings, 2021)
The article presents a classic model of consumer behaviours and contemporary concepts describing the market decisions of buyers. There are analysed changes in process of purchasing decisions observed during last times – from linear EKB model to the non-linear model of the customer's purchase path. It also lists the factors that are the main determinants of the changes observed. Using the case study analysis, the author of the article also shows the effectiveness of the methods of influencing the consumer's market decisions based on non-rational arguments. The author also predicts the directions of future research on consumer behaviour, based on the analysis of the literature of the subject and the case studies conducted.
Keywords: Consumer Behavior; Purchasing Decision; Customer's Purchase Path; EKB Model